Unveiling superior phenol detoxification and degradation ability in Candida tropicalis SHC-03: a comparative study with Saccharomyces cerevisiae BY4742 - Li, Qian; Chen, Yulei; Tang, Hao; Shu, Baichao; Zhang, Zhengyue; Tang, Jiaye; Li, Dang; Jiang, Linjia; Shen, Jiwei; Yang, Yaojun; Wang, Hanyu; Ma, Menggen (Frontiers in Microbiology, 2024)
This study examined the phenol degradation capabilities and oxidative stress responses of Candida tropicalis SHC-03, demonstrating its metabolic superiority and resilience compared to Saccharomyces cerevisiae BY4742 in a culture medium with phenol as the sole carbon source. Through comparative growth, transcriptomic, and metabolomic analyses under different phenol concentrations, this study revealed C. tropicalis SHC-03's specialized adaptations for thriving in phenol as the sole carbon source environments. These include a strategic shift from carbohydrate metabolism to enhanced phenol degradation pathways, highlighted by the significant upregulation of genes for Phenol 2-monoxygenase and Catechol 1,2-dioxygenase. Despite phenol levels reaching 1.8g/L, C. tropicalis exhibits a robust oxidative stress response, efficiently managing ROS through antioxidative pathways and the upregulation of genes for peroxisomal proteins like PEX2, PEX13, and PMP34. Concurrently, there was significant upregulation of genes associated with membrane components and transmembrane transporters, enhancing the cell's capacity for substance exchange and signal transduction. Especially, when the phenol concentration was 1.6 g/L and 1.8 g/L, the degradation rates of C. tropicalis towards it were 99.47% and 95.91%, respectively. Conversely, S. cerevisiae BY4742 shows limited metabolic response, with pronounced growth inhibition and lack of phenol degradation. Therefore, our study not only sheds light on the molecular mechanisms underpinning phenol tolerance and degradation in C. tropicalis but also positions this yeast as a promising candidate for environmental and industrial processes aimed at mitigating phenol pollution.